Agricultural Institutional Models to Support Food Crop Agribusiness Development (Case Study: Indonesia – Malaysia) - Leni Handayani; Nalini A/P Arumugam; Dirga Adetrya; Akbar Sandy (Westscience Press, 2026)
This research demonstrates the importance of identifying and developing food crop agribusiness, particularly lowland rice, in Indonesia and Malaysia. It is hoped that this research will formulate a model for developing food crop agribusiness in Indonesia and Malaysia. The research subjects were 60 respondents of rice paddy farmers consisting of 30 respondents of rice paddy farmers in Indonesia and 30 respondents of rice paddy farmers in Malaysia and registered in farmer groups, which became the object of research, namely the appropriate strategies and models in developing food crop agribusiness. Data Analysis Method To analyze the problems studied using descriptive analysis, namely providing clear and in-depth problem information interpreted according to the results of the research conducted based on theoretical support related to the research object to measure farmer perceptions by analyzing using the Likert scale method. Farmer groups in the research area not only serve as a forum for improving the quality and quantity of production, but also as a channel for introducing the latest technology, expanding market access, and improving farmer welfare through collective marketing and economic empowerment. From the Index Score obtained, there is a comparison of agricultural institutional models between Indonesia and Malaysia. From the benchmark of farmer group institutional activity, the farming subsystem (on-farm), Indonesia is higher than Malaysia. From the benchmark of production facility subsystem (Upstream), marketing & processing system (Downstream), supporting service subsystem, Malaysia is higher than Indonesia, while inhibiting factors and potential for farmer institutional development between Indonesia and Malaysia still need to be improved again so that farmers are more prosperous. In general, Malaysian agricultural institutions are more supportive in the development of food crop agribusiness than Indonesia with a score difference of 3.9%. With an index score of 73.4% higher than Indonesia's 69.5%, it shows the adoption of agricultural technology and more equitable irrigation infrastructure that ensures a more stable water supply, so that the average yield per hectare is maximized. Higher levels of use of modern agricultural mechanization (such as combine harvesters and monitoring drones) and large-scale commercial land management are more dominant in Malaysia. Farmer groups in the research area not only serve as a forum for improving the quality and quantity of production, but also as a channel for introducing the latest technology, expanding market access, and improving farmer welfare through collective marketing and economic empowerment. From the Index Score obtained, there is a comparison of agricultural institutional models between Indonesia and Malaysia. From the benchmark of farmer group institutional activity, the farming subsystem (on-farm), Indonesia is higher than Malaysia. From the benchmark of production facility subsystem (Upstream), marketing & processing system (Downstream), supporting service subsystem, Malaysia is higher than Indonesia, while inhibiting factors and potential for farmer institutional development between Indonesia and Malaysia still need to be improved again so that farmers are more prosperous. In general, Malaysian agricultural institutions are more supportive in the development of food crop agribusiness than Indonesia with a score difference of 3.9%. With an index score of 73.4% higher than Indonesia's 69.5%, it shows the adoption of agricultural technology and more equitable irrigation infrastructure that ensures a more stable water supply, so that the average yield per hectare is maximized. Higher levels of use of modern agricultural mechanization (such as combine harvesters and monitoring drones) and large-scale commercial land management are more dominant in Malaysia.